General Overview of Phenolics from Plant to Laboratory, Good Antibacterials or Not - Aldulaimi, Omar A. (Pharmacognosy Reviews)
The emergence and rapid development of seriously drug‑resistant pathogens have created the greatest danger to public health and made the treatment of infectious diseases ineffective; to control the antibiotic‑resistant microbes, the discovery of new effective antibacterials with new mechanisms of action against bacteria remains an urgent task to control the bacterial resistance. The paucity of infections in wild plants supports the role of innate defense system of plants. Many researchers nominate the natural extracts to act against bacterial resistance mechanisms, and the majority of them have now been focused on the combination of plant extracts and antibiotics to define the availability of resistance modification agents. Only very few numbers of natural products are successful to reach experiments circle beyond the in vitro assays. Phenols and phenolic acids could serve as good candidates to the natural antibacterial arsenal. The pyrogallol‑based compounds are more potent than others such as catechol or resorcinol, gallic acid, and the hydroxycinnamic acid (ferulic acid) are destructing the bacterial cell wall of Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa, leading to leakage of cellular contents. These compounds have stronger activity against Gram‑positive microorganisms, and some of them showed good synergism with antibiotics, for example, pentagalloylglucopyranose, is shown a synergism with penicillin G against methicillin‑resistant S. aureus, another example is the interesting synergism between epicatechin gallate and oxacillin where the minimal inhibitory concentrations of oxacillin reduced around 500 times by the addition of epicatechin gallate to the antibiotic.
Keywords: Antibacterial; Escherichia coli; gallic acid; Staphylococcus aureus